Tinjauan Sistematis tentang Pencetakan Makanan 3D: Perkembangan dari Konsep Menjadi Realita: A Systematic Review on 3D Food Printing: Progressing from Concept to Reality - Manivelkumar, Koushikha Namakkal; Kalpana, Chinnappan A (Universitas Airlangga, 2025)
Background: Using 3D printing technology, novel items can be created from various materials, including edible ones, addressing the growing importance of sustainable food chains and personalized nutrition. As the latest advancement in additive manufacturing, 3D printing meets diverse customer demands by producing customized food items tailored to individual nutritional needs. Objectives: This literature evaluation focuses on the applications, technical advancements, and future possibilities of 3D food printing. By assessing recent developments, the study explores its adaptability and transformative potential in addressing global issues such as sustainability and personalized nutrition. Methods: To include up-to-date and relevant data, PubMed, Google Scholar, and Scopus were searched for research on